Language Features of Women in Zoe Sugg’s Vlog a Very Homey Weekend - Pramita Tasya, Ni Ketut Ayu; Maharani, Sang Ayu Isnu; Pratiwi, Putu Ayu Asty Senja (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2025)
Women’s language in the field of sociolinguistics indicated the women’s behaviour characteristics. The women’s language is women are expected to speak in universal characteristics suggested by Lakoff (1975). The aims of this research are to analyse and describe the features of women’s language in a vlog by Zoe Sugg. The method of this research is qualitative research with a descriptive method with the data in the form of spoken utterances of YouTube vlogs, published on April 22, 2022, which consists of several vlog’s activities for instance: daily routine, fashion, and special events. The findings of this research revealed that from ten features of women’s language all features are in the vlog and also, all of the functions can be found in the vlog. The result of this study research can be applied for reference to teaching material, particularly in sociolinguistics. Keywords: Women’s Language Features, Women’s Language Functions, Vlog